Weather-driven variability in cue lure trap catches of fruit flies across cropping seasons in Kashmir and Kerala - G S, Anjana; Ahmad, Mohd Jamal; Pathrose, Berin; Mir, Sajad Hussain (Indian Journal of Plant Protection, 2026)
Fruit flies (Diptera: Tephritidae) are the most destructive pests of cucurbitaceous crops and their population dynamics is strongly influenced by weather. The present research investigated the seasonal variability of fruit fly trap catches using cue lure in two contrasting agro-climatic regions of India viz., Wadura, Kashmir having a temperate climate and Palakkad, Kerala representing tropical climate. Weekly monitoring was carried out across one cropping season of cucurbitaceous crops in Kashmir (kharif 2024) and two seasons in Kerala (rabi 2024-25 and late summer 2025). The observations revealed distinct location and season specific patters. In Kashmir, fruit fly incidence began in the 27th standard meteorological week (SMW), peaking during the 31st and 32nd SMW, with trap catches showing strong positive correlations with mean (r=+0.75), maximum (r=+0.53) and minimum(r=+0.79) temperatures, but a negative correlation with maximum relative humidity (r=-0.79). Weather parameters collectively explained 74.2% of the variation in the trap catches. In Kerala, fruit fly populations peaked during 52nd SMW of the rabi season, with maximum relative humidity showing a positive correlation (r=+0.59) and maximum temperature a negative correlation(r=-0.52). During late summer, trap catches were highest in early crop weeks and positively correlated with mean and maximum temperature (r=+0.59 and +0.67 respectively), but negatively correlated with rainfall (r=-0.86) and mean and maximum relative humidity (r=-0.68 and -0.78 respectively). The weather parameters explained 52.3% variation and 84.1% variation in fruit fly population in rabi and late summer season. These insights the need for location and season specific pest management strategies foe cucurbit production.